MTHFR Gene Mutation and Its Repercussion in the Genesis and Treatment of Depression: Case Report (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aims to report the correlation of MTHFR gene mutation with the genesis of depression and antidepressants non-response in a patient, highlighting the importance of genetic investigation and indicating the replacement of L-methylfolate as an effective treatment adjuvant. This is a case report of a patient diagnosed with major depressive disorder, refractory to pharmacological therapies, in monotherapy or combination therapy, and psychotherapy. After 1 year and 4 months of persistent residual symptoms, genetic testing of the MTHFR gene was requested with confirmation of a heterozygous double mutation of MTHFR. This gene polymorphism can result in deficiency of L-methylfolate, which is related to psychiatric diseases and refractoriness to antidepressant therapy. With the introduction of l-methylfolate 15mg, the patient reported remission of depressive symptoms in 4 months of follow-up. MTHFR gene mutations influence the action of folate, favoring depression and leading to refractory response to conventional treatment.